2019
DOI: 10.4236/ojmm.2019.94020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Resistance Patterns of Gram-Negative Uropathogens among Paediatric Patients in Nigeria

Abstract: Objective: This study aimed to detect and compare the frequency and antibiotics resistant pattern of Gram-negative uropathogens implicated in urinary tract infections (UTIs) in paediatric patients attending some hospitals in Nigeria and to proffer recommendations for its management. Methods: Based on standard procedures, midstream urine samples were collected. Urinalysis was done as a preliminary diagnosis of UTI using Combi-9 test strip. Isolation of uropathogen was done and antibiotic sensitivity test was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(32 reference statements)
3
1
0
Order By: Relevance
“…We have found that Gram-negative bacterial isolates exhibited high rates of resistance towards amoxicillin-clavulanate (89.5%), ampicillin (84.6%), tetracycline (73.7%) and co-trimoxazole (68.4%). This is in agreement with the findings of previous studies conducted in Bahir Dar, Ethiopia [ 22 , 31 ], Kenya [ 36 ] and Nigeria [ 37 ]. Our results imply that these antibiotics have only the least efficacy and hence cannot be used in an empirical therapy for the management of UTI in children in the study area.…”
Section: Discussionsupporting
confidence: 93%
“…We have found that Gram-negative bacterial isolates exhibited high rates of resistance towards amoxicillin-clavulanate (89.5%), ampicillin (84.6%), tetracycline (73.7%) and co-trimoxazole (68.4%). This is in agreement with the findings of previous studies conducted in Bahir Dar, Ethiopia [ 22 , 31 ], Kenya [ 36 ] and Nigeria [ 37 ]. Our results imply that these antibiotics have only the least efficacy and hence cannot be used in an empirical therapy for the management of UTI in children in the study area.…”
Section: Discussionsupporting
confidence: 93%
“…Among the independent variables analyzed, female participants were about three times more likely to be positive for STIs as compared with their male counterparts (p = 0.012). A similar finding was reported in Nigeria [ 31 ]. This could be due to anatomical and physiological differences.…”
Section: Discussionsupporting
confidence: 90%
“…Second, in line with other studies from Sierra Leone, West Africa, and other parts of Africa, E. coli and K. pneumonia were the most common uropathogens identified [12,[24][25][26][27]. We were surprised at the isolation of S. aureus in nine specimens.…”
Section: Discussionsupporting
confidence: 76%
“…The previous reports from Sierra Leone in other hospitals have shown high levels of resistance to TMP-SMX among uropathogens [12], a high prevalence of ESBL-producing uropathogens [11], and high levels of multidrug resistance [11], and our study adds to the evidence base. Sierra Leone is not alone in facing these problems, as high levels of resistance to TMP-SMX among uropathogens have also been reported from Ethiopia (67-86%), Egypt (58%), and Nigeria (89-100%) [26,27,31,32].…”
Section: Discussionmentioning
confidence: 99%